MixedGraphinFuzzy,Neutrosophic, and Plithogenic Graphs - Florentin Smarandache; Takaaki Fujita (Neutrosophic Sets and Systems)
Graph theory examines networks consisting of nodes (vertices) and the connections (edges) between them. Mixed graphs, which combine both undirected and directed edges, provide a versatile framework for representing relationships with symmetric and asymmetric connections across various systems. In this work, we introduce and analyze the concept of mixed graphs within the contexts of Fuzzy Graphs, Neutrosophic Graphs, and Turiyam Neutrosophic Graphs. By exploring their properties, interrelations, and potential applications, we aim to advance theunderstanding of uncertain graphs.